Rosuvastatin alleviates renal injury in cardiorenal syndrome model rats through anti-inflammatory and antioxidant pathways - Biye Zhou; Qiangguo Ao; Hua Zhao; Ping Ye (Emergency and Critical Care Medicine)
Abstract. Background. Cardiorenal syndrome is increasingly common and has been reported to be associated with inflammation and oxidative stress, and statins have anti-inflammatory and antioxidant effects. Therefore, we designed this experiment to study the preventive effect of statins on cardiorenal syndrome. The aim of the study is to investigate the effect of early rosuvastatin use on cardiorenal syndrome. Method. Forty-five Wistar rats were randomly divided into 3 groups. A unilateral nephrectomy group (Group 1), a unilateral nephrectomy + coronary ligation group (Group 2), and a unilateral nephrectomy + coronary ligation + rosuvastatin group (Group 3). Right kidney removal was performed on all rats during the first week, while Group 3 was given statin intragastric administration at 10 mg/kg/d. One month later, coronary ligation was performed on rats in Groups 2 and 3. Group 3 continued statin treatment. After feeding for 3 months and 2 days, the rats were killed; urine and blood were collected and sent to the laboratory for the determination of the urinary protein/creatinine ratio and blood lipid, creatinine, and urea nitrogen levels, respectively. Serum interleukin 1β, interleukin 6, malondialdehyde, glutathione peroxidase, angiotensin II, neutrophil gelatinase-associated lipocalin, cystatin C, and B natriuretic peptide levels were also determined. On the day before euthanasia, all rats were anesthetized and examined by cardiac ultrasound. Hematoxylin-eosin and periodic acid–Schiff staining were performed on heart and kidney sections. Results. The ejection fraction in Group 2 was lower than that in Group 1 (P < 0.01). The ejection fraction value in Group 3 was lower than that in Group 1 (P < 0.01). Interleukin-1β levels in Group 2 were higher than those in Group 1 (P < 0.01). Interleukin-1β levels in Group 3 were lower than those in Group 2 (P < 0.01). The malondialdehyde value in Group 3 was lower than that in Group 2 (P < 0.05). Histopathology showed that Group 1 had slight renal damage, renal injury was aggravated in Group 2, and renal injury was still present in Group 3, but with alleviated morphology. Conclusion. The interaction of the heart and kidneys in rats is related to inflammation and oxidation. Rosuvastatin can slow down the development of the heart-kidney interaction through anti-inflammatory and antioxidant effects.